Towards a Global Theology of Revelation - Hospital, Clifford G. (Toronto journal of theology, 1997)
It has recently been customary to group Christian attitudes toward other religions as either "exclusivist." "inclusivist" or "pluralist." The traditional Christian position has most often been exclusivist, focused on the idea that Christians have the truth and others are in error; and, more specifically, that salvation is available only through Christ. and thence only within the church. On occasion there has been a somewhat broader, incipiently inclusivist approach, which has seen the divine wisdom as given in some measure to all people. But still it was judged that the full truth is found only in Jesus Christ; and in general, the practical effects of this were the same as those of the exclusivist position: salvation,was still seen as confined to those of the Christian community.